Structural features and dopant gradients in Mg2SnXSi1-X ternary compounds. Issue 1642 (16th May 2014) - Hatzikraniotis, E.; Polymeris, G.S.; Lioutas, C.B.; Burkov, A.; Stefanaki, E-C.; Samunin, A.; Isachenko, G.; Fedorov, M.I.; Paraskevopoulos, K.M.
ABSTRACT: In the present work, a comparative study is attempted, dealing with the influence of the grain size distribution on the microstructure and the free carrier concentration in Mg2 SnX Si1-X (x=0.2) ternary compounds doped with Sb. Structural in-homogeneities were monitored by using Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM) as well as Fourier transform infrared spectroscopy (FTIR) in the reflectivity mode.